PENGARUH PEMBERIAN REWARD TOKEN EKONOMI TERHADAP KEDISIPLINAN ANAK USIA 4-5 TAHUN DI PAUD KENANGA SIAK HULU - Tarigan, Hemat; Jas, Jaspar; Chairilsyah, Daviq (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The purpose of this research was as follows:) To know the discipline of children aged 4-5 years before granting rewards token economy at PAUD Kenanga Siak Hulu. 2) To know the discipline of children aged 4-5 years after granting rewards token economy at PAUD Kenanga Siak Hulu. 3) To determine the influence of reward token economy to discipline children aged 4-5 years at PAUD Kenanga Siak Hulu. The population in this study was the children PAUD Kenanga Siak Hulu consisting of 15 children were taken from the entire population of the research sample. Collecting data using observation and documentation. Data analysis techniques used in this study is a t-test analysis techniques. From the results obtained with t = 18 963 means greater than t-table at significance level of 5% (18 963> 2145). Thus, it means Ho rejected. This means that there are influence reward token economic toward discipline children aged 4-5 years at PAUD Kenanga Siak Hulu. From this study it can be concluded that the big influence reward token economic on the discipline in children aged 4-5 years at PAUD Kenanga Siak Hulu with the percentage of 60.25%.Keywords: Delivery of token reward economic, discipline child